Kama muta: similar emotional responses to touching videos across the United States, Norway, China, Israel, and Portugal - Seibt, B.; Schubert, T. W.; Janis H. Zickfeld; Lei Zhu; Zhu, L.; Arriaga, P.; Cláudia Simão; Ravit Nussinson; Nussinson, R.; Alan Page Fiske (Journal of Cross-Cultural Psychology, 2018)
Ethnographies, histories, and popular culture from many regions around the world suggest that marked moments of love, affection, solidarity, or identification everywhere evoke the same emotion. Based on these observations, we developed the kama muta model, in which we conceptualize what people in English often label being moved as a culturally implemented social-relational emotion responding to and regulating communal sharing relations. We hypothesize that experiencing or observing sudden intensification of communal sharing relationships universally tends to elicit this positive emotion, which we call kama muta. When sufficiently intense, kama muta is often accompanied by tears, goosebumps or chills, and feelings of warmth in the center of the chest. We tested this model in seven samples from the United States, Norway, China, Israel, and Portugal. Participants watched short heartwarming videos, and after each video reported the degree, if any, to which they were “moved,” or a translation of this term, its valence, appraisals, sensations, and communal outcome. We confirmed that in each sample, indicators of increased communal sharing predicted kama muta; tears, goosebumps or chills, and warmth in the chest were associated sensations; and the emotion was experienced as predominantly positive, leading to feeling communal with the characters who evoked it.